Hungarian Stories of the Regime Change: Voices and Perspectives - Balázs, Imre József (Porównania, 2020)
Regime change narratives in Hungarian literature gained a new type of consistency around 2010, after two decades of postcommunism. The article analyses narrative strategies of novels written about the regime change, showing their tendency towards a microhistorical approach. The discussed novels include works by such minority authors as Ádám Bodor, Andrea Tompa, Sándor Zsigmond Papp, Zsolt Láng, who represent in their novels the dramatic regime change that took place in Romania in 1989.